Coevolution of Drosophila-type timeless with partner clock proteins - Bullo, Enrico; Chen, Ping; Fiala, Ivan; Smýkal, Vlastimil; Doležel, David (iScience, 2025)
Drosophila-type timeless (dTIM) is a key clock protein in fruit flies, regulating rhythmicity and light-mediated entrainment. However, functional experiments indicate that its contribution to the clock differs in various insects. Therefore, we conducted a comprehensive phylogenetic analysis of dTIM across animals and dated its origin, gene duplications, and losses. We identified variable and conserved protein domains and pinpointed animal lineages that underwent the biggest changes in dTIM. While dTIM modifications are only mildly affected by changes in the PER protein, even the complete loss of PER in echinoderms had no impact on dTIM. However, changes in dTIM always co-occur with the loss of CRYPTOCHROMES or JETLAG. This is exemplified by the remarkably accelerated evolution of dTIM in phylloxera and aphids. Finally, alternative d-tim splicing, characteristic of Drosophila melanogaster temperature-dependent function, is conserved to some extent in Diptera, albeit with unique alterations. Altogether, this study pinpoints major changes that shaped dTIM evolution.
Keywords: Neuroscience; Evolutionary biology; Genetics; Molecular biology